2006
DOI: 10.1002/prep.200600056
|View full text |Cite
|
Sign up to set email alerts
|

Study of Combustion Properties of a Solid Propellant by Highly Time‐Resolved Passive FTIR

Abstract: With a time resolution of 0.125 s and a spectral resolution of 4 cm−1, emission spectra of the combustion process of a solid propellant were recorded by highly time‐resolved passive FTIR. Some gaseous combustion products, such as H2O, CO, CO2, NO and HCl, were distinguished by the characteristic emission band of each molecule. The equation for flame temperature calculation based on the diatomic molecule emission fine structure theory was improved through judicious utilization of the spectral running number ‘m’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…These findings confirm the accumulation of nanotitania in gill tissues as observed in kidneys of rainbow trout (Scown et al, 2009). FTIR peak occurred at approximately 1400 cm-1 corresponding to the C-O stretch bonds as characterized in residual organics samples (Zhang et al, 2006). The peak at 1630 cm -1 and the broad band at 3000-3600 cm-1 are due to A c c e p t e d M a n u s c r i p t…”
Section: Discussionsupporting
confidence: 81%
“…These findings confirm the accumulation of nanotitania in gill tissues as observed in kidneys of rainbow trout (Scown et al, 2009). FTIR peak occurred at approximately 1400 cm-1 corresponding to the C-O stretch bonds as characterized in residual organics samples (Zhang et al, 2006). The peak at 1630 cm -1 and the broad band at 3000-3600 cm-1 are due to A c c e p t e d M a n u s c r i p t…”
Section: Discussionsupporting
confidence: 81%
“…Neutz and Weiser found that it is possible to separate the functional requirements for spectral flares in that they combined a high temperature payload with very little black body signature and a payload contributing in providing a selective emitter like carbon dioxide [17,18]. They combined thermites based on Al/Fe 2 O 3 , Sr(NO 3 ) 2 , and energetic organic binder to give the so-called "pyro-organic" flare [20] of propellant compositions containing nitrocellulose and nitroglycerin similar to the compositions described by Gaisbauer et al [4].…”
Section: Publicationsmentioning
confidence: 99%
“…Also, self-absorption phenomena make the determination of flame temperature and effective emissivity difficult by spectroscopic analysis [7]. In order to avoid the complexity of the problem, particularly in propellant combustion mentioned above, and for infrared radiation, spectra from product molecules in hot burnt gases of flame have been widely utilized to estimate flame temperature where thermodynamic equilibrium can be assumed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%